OP0203 In Rheumatoid Arthritis Synovitis Is Not Dominated by Polymorphic Local, but Rather by Uniform Systemic T Cell Responses. (15th July 2016) - Musters, A.; Klarenbeek, P.L.; Doorenspleet, M.E.; Esveldt, R.E.; van Schaik, B.D.; Jongejan, A.; Tas, S.W.; van Kampen, A.H.; Baas, F.; de Vries, N.
Abstract : Background: Genetic and immunological evidence clearly points to a pathogenic role of T cell clones in rheumatoid arthritis (RA). Previous studies of T cell receptor (TCR) repertoires in the synovial tissue (ST) of individual inflamed joints showed highly expanded T cell clones; however, these clones had background frequencies in peripheral blood (PB) 1 . Objectives: To gain more insight into the potential role of these expanded T cell clones in RA, and to study whether single ST biopsies and synovial fluid (SF) samples are representative for the clonal T-cell disturbances observed, we analyzed the distribution of these highly expanded T cell clones in ST and SF samples from different joints in the same patient at the same time point. Methods: In 7 RA-patients we simultaneously obtained ST biopsies from two inflamed joints via mini-arthroscopy together with paired PB and SF samples. ST biopsies were obtained from ankle or from the infrapatellar region of the knee. In 6 patients we took additional independent suprapatellar (SP) biopsies within the same knee joint. Samples were processed for RNA-based next generation sequencing. T cell clones were identified by their unique TCR β-chain sequence, the degree of expansion being expressed as a percentage of the total number of reads. To test for dissimilarity between different sites the Morisita index was used. This index originates from the field of biodiversity and gives a value between 0 and 1, values near 0 resemble no overlap between two locations while values close to 1 indicate similarity 2 . A One-tailed Mann-Whitney test was performed where applicable. Results: We identified 1, 114, 386 clones in 7, 890, 571 TCR-sequences. Only a small proportion of the clones present in ST were retrieved in the same proportion in SF (Morisita Index 0.07, SD 0.20) and PB (0.006, SD 0.14). In contrast, considerable overlap was seen if we analyzed cellular infiltrate in ST biopsies from different regions of the same joint: 0.55 (SD 0.28). An identical overlap was seen if we analyzed ST from different joints in the same patient: 0.54 (SD 0.26). This overlap was significantly different from that between ST and PB (p<0.005) and ST and SF (p<0.05). Conclusions: SF and PB T cells do not fully reflect the repertoire of dominant clones in the ST, suggesting that analysis of biopsies rather than SF or PB is preferred. ST biopsies taken from different locations within the same joint show substantial overlap suggesting that single biopsies, e.g. taken by ultrasound, show a representative snapshot of the ST T cell infiltrate. Interestingly, ST biopsies from different joints also show substantial overlap of the most dominant T cell clones in patients with active RA. This indicates that in individual patients a limited number of T cell clones dominate the adaptive immune response in the ST. Detailed cellular characterization of these clones seems warranted, and may help to devise more selective strategies for therapeutic targeting. References: Klarenbeek P, et al. Ann. Rheum. Dis. 2012;71(6):1088–1093. Wolda H. Oecologia 1981;50:296–302. Disclosure of Interest: A. Musters: None declared, P. Klarenbeek: None declared, M. Doorenspleet: None declared, R. Esveldt Employee of: BTCURE, a research project from the Innovative Medicines Initiative Joint Undertaking (grant No 115142–2)., B. van Schaik: None declared, A. Jongejan: None declared, S. Tas: None declared, A. van Kampen: None declared, F. Baas: None declared, N. de Vries Grant/research support from: BTCURE, a research project from the Innovative Medicines Initiative Joint Undertaking (grant No 115142–2).